The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1055/s-0041-1723781
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte Immune Response and T Cell Differentiation in Fontan Patients with protein-losing enteropathy

Abstract: Background Protein-losing enteropathy (PLE) is a severe complication of the Fontan circulation. There is increasing discussion about whether lymphatic dysregulation is involved as pathomechanism of PLE. This investigation focuses on the interplay between alteration of lymphatic cells and immunologic pathway alterations. Methods Micro-ribonucleic acid (miRNA) expression profiling was performed in 49 patients (n = 10 Fontan patients with PLE, n = 30 Fontan patients without PLE, and n = 9 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…The lymphatic system including lymphatic vasculature and lymph fluid represents a major player regulating immune function and tissue fluid balance. Which is of particular interest in Fontan patients, who show immunologic alterations including lymphopenia and changes in T cells and T cell subsets ( 11 ). Lymphopenia in Fontan patients has been associated with portal hypertension and PLE and an association to lymphatic malformations has been postulated ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lymphatic system including lymphatic vasculature and lymph fluid represents a major player regulating immune function and tissue fluid balance. Which is of particular interest in Fontan patients, who show immunologic alterations including lymphopenia and changes in T cells and T cell subsets ( 11 ). Lymphopenia in Fontan patients has been associated with portal hypertension and PLE and an association to lymphatic malformations has been postulated ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…The lymphatic system can be visualized in T2-weighted imaging and has led to a classification of thoracic perfusion pattern by Biko et al of four types describing the extent of lymphatic malformations, which are clinically associated with worse outcome ( 8 , 10 ). Besides changes in the lymphatic system, PLE in Fontan patients is associated with inflammation and alterations in immune response ( 11 ). However, it is difficult to predict the occurrence Fontan failure and hemodynamic changes are often misleading here.…”
Section: Introductionmentioning
confidence: 99%
“…The patients have hypogammaglobulinemia, severe lymphopenia with decreased CD4 T cell counts, and altered T cell differentiation toward memory and terminally differentiated T cells. 42 Hypogammaglobulinemia is a common finding in patients with PLE, as a result of gut protein losses. Patients with PLE might have conserved antibody responses and normal rate of infections, which depends on the severity of lymphopenia and hypogammaglobulinemia.…”
Section: Protein-losing Enteropathymentioning
confidence: 99%
“…Many studies have shown that patients post-Fontan have lymphopenia, a selective loss of CD4+ helper T cells, and hypogammaglobulinemia. [1][2][3][4] Additionally, Fontan patients are at increased risk of developing protein-losing enteropathy (PLE), the loss of protein through the intestinal mucosa, which has been shown to significantly alter the immunophenotype of these individuals 2 via the loss of immunoglobulins; often necessitating IVIG replacement infusions in many of these patients. Lymphopenia, on the other hand, can occur in the presence or absence of PLE.…”
Section: Introductionmentioning
confidence: 99%
“…A depressed immune system is one of these sequelae that has been well described 1–3 ; however, the mechanisms and clinical implications of these findings have yet to be fully elucidated, particularly as it relates to heart transplantation (HTx) in this patient population. Many studies have shown that patients post‐Fontan have lymphopenia, a selective loss of CD4+ helper T cells, and hypogammaglobulinemia 1–4 . Additionally, Fontan patients are at increased risk of developing protein‐losing enteropathy (PLE), the loss of protein through the intestinal mucosa, which has been shown to significantly alter the immunophenotype of these individuals 2 via the loss of immunoglobulins; often necessitating IVIG replacement infusions in many of these patients.…”
Section: Introductionmentioning
confidence: 99%